Pengaruh Faktor Sosiodemografi terhadap Frekuensi Pemberian MP-ASI di Jawa Timur - Adila Ainun Zahra; Mahmudah Mahmudah (Yayasan Literasi Sains Indonesia, 2026)
Complementary feeding (MP-ASI) frequency is a key indicator of child nutrition among children aged 6–23 months. This study aimed to analyze the influence of sociodemographic factors on the frequency of complementary feeding among children aged 6–23 months in East Java using data from the 2025 National Socioeconomic Survey (SUSENAS). This is an observational analytic study with a cross-sectional design. The sample consisted of 1,386 children aged 6–23 months in East Java. The dependent variable was the frequency of complementary feeding in the past 24 hours, while independent variables included child age, child sex, maternal education, maternal employment status, number of children, household head education, household expenditure quintile, and place of residence. Analysis was performed using Poisson regression with robust error standard to accommodate complex survey design and correct for underdispersion (dispersion value = 0.36). Results showed that child age (β = 0.011; p < 0.001; IRR = 1.011) and number of children (β = −0.039; p = 0.020; IRR = 0.962) were the only significant predictors in the final model. Each additional month of child age increased complementary feeding frequency by 1.1%, while each additional child in the household decreased frequency by 3.8%. Other sociodemographic variables did not show significant influence. These findings highlight the importance of age-responsive feeding practices and targeted support for mothers with multiple children in East Java.